2007
DOI: 10.1080/02705060.2007.9665052
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Fluctuating Temperatures and Gill Parasites on Reproduction of the Fountain Darter,Etheostoma fonticola

Abstract: We assessed the effects of fluctuating temperature and gill parasitism on egg and larval production of the endangered fountain darter (Etheosfoma fonticola). Fountain darters, with and without the exotic digenetic trematode Cen~rocestrrs formosanus. were exposed in the laboratory to constant (24°C) and fluctuating (24 to 26°C. 26 to 28°C. and 28 to 30°C) water temperatures for 2 1 d. No differences were detected between the number of eggs produced (P = 0.78) or number of larvae produced (P = 0.1 1) between fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Stenothermal artesian springs throughout the basin provide refugia for a number of non‐native taxa introduced by illegal dumping of ornamental organisms and by other means, including a parasitic trematode (Mitchell et al ., 2005), molluscs (Karatayev et al ., 2009) and fishes (Thomas et al ., 2007). Potential effects of introduced organisms on aquatic systems and fishes within the basin only recently have been explored (McDonald et al ., 2006, 2007; Cohen, 2008; Pray, 2009; Scott, 2009). Collectively, water quality and introduced taxa have caused localized problems within the basin, and their contribution to fish assemblage changes through time cannot be easily separated from flow modifications.…”
Section: Discussionmentioning
confidence: 99%
“…Stenothermal artesian springs throughout the basin provide refugia for a number of non‐native taxa introduced by illegal dumping of ornamental organisms and by other means, including a parasitic trematode (Mitchell et al ., 2005), molluscs (Karatayev et al ., 2009) and fishes (Thomas et al ., 2007). Potential effects of introduced organisms on aquatic systems and fishes within the basin only recently have been explored (McDonald et al ., 2006, 2007; Cohen, 2008; Pray, 2009; Scott, 2009). Collectively, water quality and introduced taxa have caused localized problems within the basin, and their contribution to fish assemblage changes through time cannot be easily separated from flow modifications.…”
Section: Discussionmentioning
confidence: 99%
“…, 2007). Rapid changes of temperature can be stressful to organisms (McDonald et al. , 2007), inducing loss of coordination (Aslanidi et al.…”
Section: Introductionmentioning
confidence: 99%
“…Similar to altitudinal gradients (Taniguchi et al, 1998; Taniguchi & Nakano, 2000), water temperature is a suggested mechanism in regulating richness, abundances, and densities of spring-associated fishes and riverine-associated fishes (Hubbs, 1995; Kollaus & Bonner, 2012) with spring-associated fishes being potentially more fit in stenothermal habitats and riverine-associated fishes being potentially more fit in eurythermal habitats. Dissimilar to altitudinal gradients, spring-associated fishes and riverine-associated fishes do not represent previously researched cold-water and warm-water forms with overlapping tolerances, but both are warm-water forms having similar temperature tolerances (Hagen, 1964; Brandt et al, 1993), and similar reproductive tolerances (Bonner et al, 1998; McDonald et al, 2007). In marine systems, species in stenothermal habitats might select away from eurythermal enzymes and proteins (Graves & Somero, 1982) and select for proteins and enzymes that are more energy efficient within a narrow range of temperatures (Pörtner, Peck & Somero, 2007), whereas species in eurythermal habitats are suggested to conserve temperature-dependent enzymes and proteins that enable tolerance of wide-ranging water temperatures (Somero, Dahlhoff & Lin, 1996).…”
Section: Introductionmentioning
confidence: 89%